Adaptive optics for optical microscopy [Invited] - Zhang, Q; Hu, Q; Berlage, C; Kner, P; Judkewitz, B; Booth, M; Ji, N (Optica, 2023)
Optical microscopy is widely used to visualize fine structures. When applied to bioimaging, its performance is often degraded by sample-induced aberrations. In recent years, adaptive optics (AO), originally developed to correct for atmosphere-associated aberrations, has been applied to a wide range of microscopy modalities, enabling high- or super-resolution imaging of biological structure and function in complex tissues. Here, we review classic and recently developed AO techniques and their applications in optical microscopy.